Quantitative Determination of CMV DNA Using a Combination of Competitive PCR Amplification and Sandwich Hybridization. (October 1998) - Alexandre, I.; Zammatteo, N.; Ernest, I.; Ladriere, J.-M.; Le, L.; Hamels, S.; Chandelier, N.; Vipond, B.; Remacle, J.
A quantitative PCR method is proposed that combines the use of a competitive internal standard with the sandwich hybridization of the products. The variability of the PCR efficiency was corrected using a specifically designed internal standard, competitive not only for the PCR amplification, but also for the hybridization on capture probes fixed onto microwells. The design of such standard gave a dynamic range extending from 30–1 million copies of target DNA when the internal standard copy number was fixed to 1000 using a simple colorimetric detection. The assay was independent from the number of PCR cycles, which indicates a true competition between the standard and the template DNA. The assay was developed for a cytomegalovirus (CMV) DNA sequence and is illustrated by the quantification of CMV in a culture sample.